Evaluation of the Psychometric Properties of Jebsen Taylor Hand Function Test (JTHFT) in Italian Individuals With Multiple Sclerosis - Berardi, Anna; Galeoto, Giovanni; Pasquali, Federica; Baione, Viola; Crisafulli, Sebastiano Giuseppe; Tofani, Marco; Tartaglia, Matteo; Fabbrini, Giovanni; Conte, Antonella (Frontiers in Neurology, 2022)
Introduction The Jebsen Taylor Hand Function Test (JTHFT) is a non-diagnostic assessment scale for hand and upper limb dexterity that is commonly used in various countries around the world for diseases, such as muscular dystrophy, stroke, spinal cord injury, Parkinson, carpal tunnel syndrome, and rheumatoid arthritis. This study aimed to evaluate the psychometric properties of the JTHFT in Italian adults with Multiple Sclerosis (MS). Materials and Methods The test's internal consistency was evaluated with Cronbach's alpha, whereas its concurrent validity was evaluated by comparing the JTHFT with the Health Assessment Questionnaire (HAQ) and by calculating Pearson's correlation coefficient. Results The JTHFT was administered to 29 Italians with MS. The Cronbach's alpha showed that the nondominant hand has a value of 0.76 and 0.91 for the dominant hand. Pearson's correlation coefficient showed significant correlations between JTHFT and HAQ. Discussion The JTHFT is a reliable tool to evaluate the functionality of the upper limb and hand in patients with MS. This tool is useful for testing the effectiveness of a treatment in various diseases. The results obtained in this study are coherent with previous studies that are conducted in populations with different diseases. In particular, the correlation between JTHFT and HAQ showed that a disability related to the upper limbs can often have repercussions, not only on activities of daily living, but also on walking. Based on this correlation, the motor deficits that emerged may be linked to a brain marrow disease rather than a spinal disease, even if an essential deepening can confirm this hypothesis.